A cross-sectional study of evidence-based practice and association factors among nurses in public health facilities of Dessie city, Northeast Ethiopia - Yimam, Tariku; Mekonnen, Asnakew Molla; Tsega, Yawkal; Gebeyehu, Endalkachew Mesfin (Frontiers in Public Health, 2025)
BackgroundEvidence-based practice (EBP) is essential in modern healthcare to improve patient outcomes and enhance the quality of care. Nurses play a crucial role in implementing EBP in clinical settings, yet its utilization remains suboptimal in many healthcare facilities, particularly in resource-limited settings. However, nursing practice in Ethiopia often relies on experience, tradition, intuition, common sense, and untested theories. Additionally, there is a lack of information on the implementation of EBP by nurses in Ethiopia, particularly in the study area. However, there is limited empirical evidence assessing the level of EBP implementation and the associated factors among nurses in these facilities. Therefore, this study aims to assess evidence-based practice and association factors among nurses in public health facilities of Dessie city, Northeast Ethiopia.MethodsAn institutional-based cross-sectional study was conducted among 442 nurses in public health facilities of Dessie City from January 17 to February 17, 2023. A stratified random sampling technique was used to select participants. Data were collected using a structured self-administered questionnaire and analyzed using bi-variable and multivariable binary logistic regression. Adjusted odds ratios (AOR) with 95% Confidence Intervals (CI) were calculated, and statistical significance was declared at p < 0.05.ResultsThe prevalence of good Evidence-Based Practice (EBP) utilization among nurses was 37.6% (95% CI: 32.9–42.2%), indicating a low level of adoption. The mean (±SD) age of the participants was 41.34 (±12.86) years. Key factors significantly associated with EBP implementation included: Knowledge of EBP: Nurses with good knowledge were six times more likely to implement EBP (AOR = 6.01; 95% CI: 3.78, 9.55). Type of Health Facility: Nurses working in hospitals were nearly three times more likely to practice EBP compared to those in health centers (AOR = 2.89; 95% CI: 1.45, 5.76). Attitude towards EBP: Nurses with a favorable attitude were 3.4 times more likely to engage in EBP (AOR = 3.41; 95% CI: 2.04, 5.71). Additionally, barriers to EBP adoption included limited resources (34.4%), high workload (27.5%), and lack of internet access at the workplace (68.7%). Less than 10% of nurses reported using nursing journals as sources of evidence, while 73.4% relied on information from coworkers.ConclusionThis study highlights a low prevalence of EBP utilization among nurses in Dessie City. The strong association between EBP adoption and factors such as knowledge, attitude, and type of health facility suggests the need for targeted interventions. Improving nurses’ access to EBP training, research resources, and institutional support could significantly enhance EBP implementation, leading to better patient care and health outcomes.